Navisalvia. The Saviour of Great Mother's ship - Vilogorac Brčić, Inga (Array, 2012)
Claudia Quinta is the heroine of the legend about the arrival of the Great Mother Cybele from Phrygia to Rome. Greek and Roman writers often mentioned her. She was even divinised as the goddess Navisalvia, worshipped beside the Great Mother. That is evidenced by three votive altars uncovered in Rome. Work presents literary and epigraphic sources related to Claudia Quinta.